Solid phase extraction: Applications to the chromatographic analysis of vegetable oils and fats - P. M. Panagiotopoulou; M. Tsimidou (Grasas y Aceites, 2002)
Applications of solid-phase extraction for the isolation of certain lipid classes prior to chromatographic analysis are given. More information was found for sterols and related compounds, polar phenols and contaminants such as polycyclic aromatic hydrocarbons. Detailed analytical protocols are presented and discussed in many cases.